2014
DOI: 10.1111/1744-7917.12169
|View full text |Cite
|
Sign up to set email alerts
|

Soybean aphid intrabiotype variability based on colonization of specific soybean genotypes

Abstract: The soybean aphid, Aphis glycines Matsumura (Hemiptera: Aphididae), is one of the most destructive insect pests on soybeans in the United States. One method for managing this pest is through host plant resistance. Since its arrival in 2000, 4 aphid biotypes have been identified that are able to overcome soybean aphid resistance (Rag) genes. A soybean aphid isolate collected from Moline, Illinois readily colonized soybean plants with the soybean aphid resistance gene Rag2, unlike biotypes 1 and 2, but similar t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
4
6
0
Order By: Relevance
“…We agree with Pawlowski et al (2015), who concluded that any new soybean cultivars should be tested at multiple locations to ensure that they are exposed to as many biotypes as possible. Wenger and Michel (2013) concluded that soybean aphid biotypes were genetically indistinguishable across a large region because of high rates of interpopulation immigration and admixture.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…We agree with Pawlowski et al (2015), who concluded that any new soybean cultivars should be tested at multiple locations to ensure that they are exposed to as many biotypes as possible. Wenger and Michel (2013) concluded that soybean aphid biotypes were genetically indistinguishable across a large region because of high rates of interpopulation immigration and admixture.…”
Section: Discussionsupporting
confidence: 79%
“…Their two isolates (Biotype 3) differed in population growth by 3 to 10 times. Thus, in 2013, we observed similar differences across isolates of Biotype 3, as did Pawlowski et al (2015). 6b-6d).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations